Tanggung Jawab Ahli Waris terhadap Hutang Pewaris Berdasarkan Hukum Islam - Ilyas Ilyas (Universitas Syiah Kuala, 2011)
ABSTRACT: Article 175 (2) on the Islamic Law Compilation states that the responsibility of inheritor towards the loan belongs to bequeathor is limitted to amount of the inheritance property. In Islamic Law Compilation does not explain completely regarding the loan of the bequeathor that in what kind of loan will be the responsibility of the heirs. In practice, the dispute between the heirs and the people providing the loan. The loan between them happens without written roof of argument but the contract is mode vocally; hence causes the dispute between them. This article aims to explain the biews of the priest regarding the obligation of the heirs to pay the loan. The research shows that the obligation of the heirs to pay the loan must be paid first before the property divided to the based on each portion. However, the payment of the loan should not have bad impact on the heirs that receive te inheritance property. The Responsibility of Inheritor Towards Bequeathor Loan Based on Islamic Law